2019
DOI: 10.1504/ijmor.2019.096975
|View full text |Cite
|
Sign up to set email alerts
|

A new short-term energy price forecasting method based on wavelet neural network

Abstract: A wavelet neural network (WNN) is proposed for short-term price forecasting (STPF) in electricity markets. Back propagation algorithm is used for training the wavelet neural network for prediction. Weights in the back propagation algorithm are usually initialised with small random values. If the random initial weights happen to be far from a suitable solution or near a poor local optimum, training may take a long time or get trapped in the local optimum. In this paper, we show that WNN has acceptable predictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Their results showed that the hybrid model significantly outperformed the individual models. Keynia et al proposed a model that uses the wavelet transform and neural networks to predict the electric water boilers' energy consumption [178]. The wavelet transform is used to decompose the load series into different frequency load demand components, and neural networks are used to predict each decomposed series.…”
Section: Hybrid Approachesmentioning
confidence: 99%
See 3 more Smart Citations
“…Their results showed that the hybrid model significantly outperformed the individual models. Keynia et al proposed a model that uses the wavelet transform and neural networks to predict the electric water boilers' energy consumption [178]. The wavelet transform is used to decompose the load series into different frequency load demand components, and neural networks are used to predict each decomposed series.…”
Section: Hybrid Approachesmentioning
confidence: 99%
“…This allows for the comparison of prediction accuracy across different datasets. Furthermore, most deterministic and traditional probabilistic and data-driven stochastic methods use MAPE and RMSE to evaluate their models [6,178,179]. Lower MAPE values indicate better prediction accuracy, facilitating easy model comparisons.…”
Section: Statistical Evaluation Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…; Q is the number of hidden nodes, and f and g are the transfer functions that are often used as a logistic function 7 .…”
Section: Regression Modellingmentioning
confidence: 99%